Pollen morphological assessment of specific selected species of district Sheikhupura, Punjab, Pakistan under LM and SEM. Issue 5 (31st December 2020) - Alam, Ayesha; Shaheen, Shabnum; Sarwar, Samina; Jaffer, Mehwish; Saba, Malka; Hanif, Muhammad; Sajjad, Sumera; Khan, Farah
Abstract: Around 30 pollen samples, 16 families and 25 genera that were gathered, identified and preserved from 6 different localities of District Sheikhupura. Light and scanning electron microscopy was done for all collected flora. Out of the total samples, 43% specie was identified as herbs, 23% as shrubs, and 33% were identified as trees. The flora was both wild and cultivated. Wild plants were 33%, cultivated 40% and 26% of them were both wild and cultivated. Qualitative and Quantitative survey of pollens revealed polar shape of pollens were 37% spheroidal, 20% prolate spheroidal, 17% oblate spheroidal, remaining were rectangular and pecolpate. Sexine and nexine were available in 100% of samples. Thirty‐three percentage of pollen grains were having spines on them. The presence of spines on pollen grains represents the evolutionary relationship amongst the plants. Current study was conducted to record and analyze palynomorphic diversity in district Sheikhupura, Punjab, Pakistan. Abstract : This research was focused to evaluate the significance of palynological parameters as an identification tool under light and scanning electron microscopy. A large number of diversity was observed in the studied taxa based on their palynological features, which results that it is a worthwhile tool not only in identification but also in delimitation of taxa.